1999
DOI: 10.1016/s0886-3350(99)00090-5
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal fluctuations in corneal topography 10 years after radial keratotomy in the prospective evaluation of radial keratotomy study

Abstract: Diurnal fluctuations in corneal topographic indexes can be used to evaluate the diurnal fluctuations in refraction and visual acuity after RK. The study findings provide statistical support for the idea that IOP contributes to the diurnal fluctuation in visual acuity after RK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
0
20
0
6
Order By: Relevance
“…1 Long-term follow-up has shown that ectatic radial keratotomy (RK) patients experience corneal instability, characterized by visual fluctuations, increase in spherical equivalent (SE), and hyperopic shifts. 2,3 Hyperopic laser-assisted in situ keratomileusis (LASIK) has been shown to be effective in RK patients; however, cylindrical errors are difficult to correct, and astigmatic correction regresses over time. 4 Hence, visual rehabilitation in RK patients is still considered a challenge, regardless of whether laser-assisted techniques, phakic intraocular lenses (IOLs), or pseudophakic IOLs (monofocal, multifocal, multifocal toric, or piggy-back) are used.…”
mentioning
confidence: 99%
“…1 Long-term follow-up has shown that ectatic radial keratotomy (RK) patients experience corneal instability, characterized by visual fluctuations, increase in spherical equivalent (SE), and hyperopic shifts. 2,3 Hyperopic laser-assisted in situ keratomileusis (LASIK) has been shown to be effective in RK patients; however, cylindrical errors are difficult to correct, and astigmatic correction regresses over time. 4 Hence, visual rehabilitation in RK patients is still considered a challenge, regardless of whether laser-assisted techniques, phakic intraocular lenses (IOLs), or pseudophakic IOLs (monofocal, multifocal, multifocal toric, or piggy-back) are used.…”
mentioning
confidence: 99%
“…Tal observação corrobora com o conceito de que a instabilidade da córnea após RK esteja relacionada com variações da pressão ocular. (17) É importante notar que não houve correlações com a IOPg. Tais achados suportam nossa hipótese de que a inconsistência nas associações entre as variações da hipermetropia e da pressão ocular, observada em alguns estudos, (15) está relacionada com alterações das medidas de tonometria de aplanação de Goldmann (TAG) após RK.…”
Section: Discussionunclassified
“…(14,15) A instabilidade da córnea foi documentada por meio de topografia, cujos índices se relacionaram melhor que a ceratometria central com a flutuação refracional e da acuidade visual não corrigida. (16,17) Há evidências de que a instabilidade da córnea após RK que leva à hipermetropia esteja relacionada com variações da pressão ocular. (17) Em um estudo experimental, alterações induzidas na pressão ocular foram relacionadas com o grau de aplanamento da córnea em coelhos submetidos à RK.. (18) Entretanto, dados conflitantes foram encontrados em outros estudos, que falharam em correlacionar as alterações da pressão ocular ao longo do dia, com as variações refracionais e de acuidade visual encontradas.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The development of a hyperopic shift and diurnal fluctuations in visual acuity are common and troublesome side effects after this refractive surgery procedure. [1][2][3][4] The development of high astigmatism is a less common side effect. 1,5 Implantation of an Artisan toric phakic or aphakic intraocular lens (IOL) (Ophtec BV) is another option to correct astigmatic error, allowing spherical and cylindrical correction in a single procedure.…”
mentioning
confidence: 99%